2001
DOI: 10.1007/s101520000058
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ultraviolet radiation on the planktonic community of a shallow, eutrophic estuary: results of mesocosm experiments

Abstract: This paper describes the results of pelagic mesocosm experiments designed to test the effects of enhanced and reduced ultraviolet radiation (UV) on the planktonic community of a Baltic Sea estuary. The Darss-Zingst estuary consists of a series of brackish lagoons with high concentrations of chlorophyll and dissolved organic matter. The shallow depth of the estuary ensures that organisms in the water are regularly exposed to high levels of photosynthetically active radiation (PAR) and UV. During the summer of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…This lack of effect of enhanced UV-B for pigments or cell abundance has been observed frequently in studies that use stirred mesocosms (e.g. Keller et al 1997, Wängberg et al 1999, Forster & Schubert 2001, and probably reflects a moderating influence of mixing when repair is present (Helbling et al 1992, Neale et al 1998, Fouilland et al 2003. The presence of at least one such repair mechanism (D1 turnover) was ascertained in our 3 sites (Bouchard et al 2005).…”
Section: Site-specific Variations In Phytoplankton Sensitivity To Uv-mentioning
confidence: 98%
“…This lack of effect of enhanced UV-B for pigments or cell abundance has been observed frequently in studies that use stirred mesocosms (e.g. Keller et al 1997, Wängberg et al 1999, Forster & Schubert 2001, and probably reflects a moderating influence of mixing when repair is present (Helbling et al 1992, Neale et al 1998, Fouilland et al 2003. The presence of at least one such repair mechanism (D1 turnover) was ascertained in our 3 sites (Bouchard et al 2005).…”
Section: Site-specific Variations In Phytoplankton Sensitivity To Uv-mentioning
confidence: 98%
“…Some outdoor mesocosms studies showed little UVR effects on chlorophyll a (Chl a) content (Halac et al 1997;Wängberg et al 1999;Whitehead et al 2000). On the other hand, Forster et al (2001) working with phytoplankton of the Darss-Zingst estuary in the Baltic Sea found higher Chl a concentration in samples that did not receive UVR, as also observed in the experiments www.intechopen.com Long-Term UVR Effects Upon Phytoplankton Natural Communities of Patagonian Coastal Waters 231 carried out by Keller et al (1997) with communities off Narragansett Bay. At the community level, UVR impact is frequently translated onto changes in the taxonomic composition towards more tolerant species or changes in size distribution.…”
Section: Assessment Of Uvr Effects Upon Phytoplankton Over Long-term mentioning
confidence: 60%
“…Indirect effects of UVR such as the breakdown (photolysis / photodegradation) of dissolved organic matter (DOM) (Osburn and Morris 2003) can be either beneficial for organisms by means of increasing nutrient availability, or detrimental, by increasing water transparency so cells receive more irradiance (Cooke et al 2006). It is also known that the interaction of UVR and other factors -e.g., nutrient availability, vertical mixing, changes in temperature, supersaturating oxygen concentrations or high pH values, may strongly condition the observed results (Forster and Schubert 2001;Neale et al 2003;Beardall et al 2009 and references therein) as compared to those obtained considering only UVR. This is due to the synergic or antagonistic nature of the interactions between UVR and those other factors (Dunne 2010).…”
Section: Introductionmentioning
confidence: 78%
“…Mesocosms differ from microcosms in their fundamental concepts. The arrangement of a mesocosm allows assay control, without the mentioned limitations and confounding factors from microcosms, and has been used by many authors (Davies et al, 1995;Forster and Schubert, 2001;Moriñigo et al, 1990;Pommepuy, et al, 1996b;Rhodes, 1988;1990). However, mesocosms cannot provide full access to real aquatic ecosystems, promoting both bacterial species' selective growth and grazing, distorting the community structure (Beardsley et al, 2003).…”
Section: The Scale Of the Studiesmentioning
confidence: 99%
“…However, mesocosms cannot provide full access to real aquatic ecosystems, promoting both bacterial species' selective growth and grazing, distorting the community structure (Beardsley et al, 2003). For example, Forster and Schubert (2001) used a robust 1-m 3 mesocosm to test the effects of enhanced and reduced ultraviolet radiation (UV) on the planktonic community. These authors encountered smaller zooplankton population densities (rotifers and Copepods) that increased rapidly to populations that were denser than those observed in the estuary, probably due to the absence of predators like fish and larger zooplankton.…”
Section: The Scale Of the Studiesmentioning
confidence: 99%